Improving Reading Comprehension of the Eighth-Grade Students of Junior High School at Lore Peore through Napu Folktales - Vio Gita Mengkido; Nadrun Nadrun; Desrin Lebagi; Hasna Hasna (Journal of English Language and Education, 2026)
Reading comprehension is an essential skill for English language learners, yet junior high school students experience difficulties in understanding narrative texts because of limited vocabulary, low reading motivation, and insufficient exposure to culturally relevant reading materials. Integrating local folktales into English instruction may enhance students’ comprehension. This research aims to investigate the effectiveness of Napu folktales in improving the reading comprehension of eighth-grade students at SMP Negeri 2 Lore Peore. A quantitative pre-experimental one-group pre-test-post-test design was used. The participants consisted of 40 eighth-grade students selected through total sampling. Because the population at SMP Negeri 2 Lore Peore was fewer than 100 students, 20 students from SMP Negeri 1 Lore Peore were included to complete the sample. Data were collected using a reading comprehension test consisting of 20 multiple-choice questions and 5 essay questions. Data were analyzed using descriptive statistics and a paired-samples t-test with SPSS version 25. The findings revealed a statistically significant improvement in students’ reading comprehension, with the mean score increasing from 30.0250 in the pre-test to 72.5750 in the post-test (p 0.05), indicating that the use of Napu folktales effectively improved students’ reading comprehension and promoted appreciation of their local cultural heritage.